Extraction and Characterization of Pectin from Snake Fruit Peel via Maceration - Raafi Akbar Putra Purnomo; Yeti Rusmiati Hasanah; Neni Damajanti (Universitas Muhammadiyah Purwokerto, 2024)
The high consumption of fruit flesh from the snake fruit is not in line with the utilization of fruit peels, which are often considered organic waste that goes to waste. The lack of optimal utilization of fruit peels as organic waste can open up opportunities to develop other alternatives, such as using fruit peels as a source of pectin. The extraction of pectin from fruit peels is carried out using the maceration extraction method with citric acid as the solvent. This research aims to determine the effect of the solvent material ratio and solvent concentration, as well as to understand the characteristics of the resulting pectin product. The results of this study indicate that among the variations in the ratio of materials and solvents, the highest %yield was achieved at a ratio of 1:40 (gr/mL) with a %yield value of 13.15%. In the variations of solvent concentration, the highest pectin %yield was at a concentration of 10% with a %yield value of 17.5%. The characteristics of the produced pectin were the highest equivalent weight of 114.94 mg, the highest methoxyl content of 9.92%, and the highest galacturonic acid content of 1063.04%. Functional group analysis using FTIR showed the presence of the O-H functional group at a wavelength of 3255 cm-1, the aliphatic C-H functional group at a wavelength of 2808 cm-1, the carboxyl (C=O) functional group at 1838 cm-1, and the methyl C-H functional group at a wavelength of 1442 cm-1. Therefore, the best research results were found at 1:40 and a solvent concentration of 10% with the highest %yield, equivalent weight, methoxyl content, and galacturonic acid content